Virtual Reality as a Clinical Modality for Retraining Balance and Mobility. - McEwen, Daniel (Université d'Ottawa / University of Ottawa, 2017)
Physical rehabilitation of individuals who are experiencing a disabling illness or have survived a traumatic injury (i.e. stroke) must seek to train the body’s structures and functions to reduce disability (activity limitations, participation restrictions) (Stucki, 2005). Figure 1 represents a modified version of the International Classification of Functioning (ICF), Disability and Health (World Health Organization, 2002). This figure illustrates how, for example, a stroke impacts the body structures and functions (e.g. muscle recruitment) which influences the ability to complete activities (e.g. gait) ultimately restricting participation in all areas of life (e.g. employment). The ICF model presents a framework for clinical practice and rehabilitation research studies. Although it has been shown to be strongly correlated (Schmid, Van Puymbroeck, et al., 2013) the concept of function cannot always be directly correlated with the concept of quality of life (Stucki, 2005) as the individual may not perceive, for example, impaired balance and mobility as detrimental to their quality of life. However, reduced function does put an individual at further risk of complications including falls and injuries from compensatory mechanisms and therefore must be addressed. The focus of this thesis is the study of the potential benefits of an exercise modality (virtual reality) to encourage restoration of the body’s structures and functions for individuals post-stroke. As the individuals engage in physical rehabilitation through exercise, there may be improvements on the individual’s abilities as seen through measurements of the control of posture and walking. The thesis comprises four studies, two of which have been published in peer reviewed journals. The progression of studies attempts to characterize outcomes following the use of virtual reality training in clinical populations (dementia and stroke) to address impairments to the body structures and functions (e.g. mobility) as measured by both clinical measures of activity and laboratory based measures of balance and to elucidate a possible mechanism (focus of attention) that makes training in a virtual environment effective.
Keywords: Stroke; Virtual Reality; Balance; Mobility